2019
DOI: 10.1055/s-0039-1683430
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery of Cavernous Sinus Meningiomas

Abstract: Objective Microsurgical resection of cavernous sinus meningiomas (CSM) is associated with a high rate of incomplete resection, recurrence, and the risk for permanent, severe cranial nerve deficits. Stereotactic radiosurgery (SRS) has evolved as alternative treatment for primary and recurrent CSM. Here, we report about the long-term clinical and radiological follow-up (FU) of a unique cohort of patients with CSM treated with LINAC or Cyberknife based SRS. Methods In this single-center retrospective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Our study confirms the high rate of tumor control (> 90%) and effectiveness of SRS, as reported in many other series [ 7 , 8 , 19 , 20 ]. However, the influence of age on tumor control in benign brain tumors is currently not fully understood.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirms the high rate of tumor control (> 90%) and effectiveness of SRS, as reported in many other series [ 7 , 8 , 19 , 20 ]. However, the influence of age on tumor control in benign brain tumors is currently not fully understood.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to micro-neurosurgery, stereotactic radiosurgery (SRS) has evolved as a generally accepted effective therapeutic option, especially for meningiomas and schwannomas. Meanwhile, several studies have reported data on long-term follow-up with tumor control rates exceeding 90% and associated mild toxicity [4][5][6][7][8]. For patients with locally inoperable tumors or patients deemed ineligible for surgery due to medical reasons, SRS such offers a valuable treatment alternative.…”
Section: Introductionmentioning
confidence: 99%
“…The SRS planning was carried out using the software STP (STP 3.3 and 3.5, Howmedica Leibinger, Freiburg, Germany). Subsequently, the radiosurgical treatment was performed using a linear accelerator as previously described [ 7 , 8 ]. In brief, dose application was performed with circular collimators fitted to an adapted linear accelerator (Philips SL 75/20 at 9 MV or Elekta Sli25 at 6 MV).…”
Section: Methodsmentioning
confidence: 99%
“…In their review of the outcomes of large radiosurgical series, Fariselli et al [51] showed progression free survival at 5 and 10 years of 80%-100% and 73%-98%, respectively, and a radiological volume reduction was observed in 29-69% of cases. No mortality was described as secondary to radiation therapy, while the reported morbidity included new neurologic symptoms or symptoms of neurotoxicity (optic neuropathy, pituitary dysfunction, diplopia, and radiation-induced edema), which ranged from 6% to 27.5% [52][53][54][55] . A meta-analysis comparing primary RS vs. surgery followed by adjuvant RS showed a lesser rate of neurological morbidity in the primary RS group (27.5% vs. 59.6%) [55] .…”
Section: Combined and Adjuvant Strategiesmentioning
confidence: 99%